ISOLASI, UJI AKTIVITAS, DAN AKTIVITAS SPESIFIK ENZIM SELULASE Penicillium sp. LBKURCC27 SEMIMURNI MELALUI PENGENDAPAN (NH 4 ) 2 SO 4 - M. Sarip; T. T. Nugroho; H.. Y. Teruna (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Enzyme activity of cellulase can be concentrated by ammonium sulfate ((NH 4 ) 2 SO 4 )precipitation. The concentration was carried out by adding ((NH 4 ) 2 SO 4 ) 80% saturatedprecipitation. The precipitated enzyme was redisolved in 1/70 of the original crude extractvolume. Enzyme activity of cellulase was assayed using CMC and avicel as the substrate.The results showed that in the concentrated enzyme preparation, the CMCase wasincreased 12 fold and enzyme activity of avicelase increased 3 fold. Activity and specificactivity of the final CMCase preparation were 1.1160±0,0622 U/mL and 7.43±0,417 U/mg,respectively. Activity and specific activity of avicelase preparation were 0.0520±0.0735U/mL and 0.34±0.487 U/mg, respectively.